(untitled) (Tempo e Argumento, 2026)
This work addresses a past that remains strikingly present when memories of the Brazilian Northeastern backlands are brought to the fore. It concerns the outlaw way of life more widely known simply as cangaço. Its aim is to problematize different forms through which this past has been updated over time, especially between the early twentieth century and the beginning of the twenty-first century, noting distinct ways of seeing and narrating the subject that reveal traces of coloniality and decoloniality of being, power, and knowledge in confrontation. Drawing on discussions aligned with the field of contemporary history, I argue that this approach allows us to trace readings of this past that range from the naturalization of the animalization of these lives to the emphasis on struggles against the dehumanization of their bodies in the present, through images that mark the life and death of male and female cangaceiros. With such reflections, the text seeks to contribute to the debate on the subject, as it deals not only with conflicts around its past but also with disputes over how its legacy is addressed in the present and for the future.